The Influence of Fashion Trends, Product Quality, and Price Perception on Purchase Intention - Andrian, Fery (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
As one of the countries with the largest Muslim population in the world, Indonesia holds significant market potential in the Muslim fashion industry. The growing demand for fashion products that align with Islamic values has encouraged the development of local brands such as Modeco Busana. This study aims to analyze the influence of fashion trends, product quality, and price perception on purchase intention for Modeco Busana products. The sample of this explanatory quantitative research consisted of 161 respondents selected using purposive sampling with the criteria of being over 17 years old, aware of Modeco Busana, and residing in DKI Jakarta. The data were collected through questionnaires and analyzed using multiple linear regression in IBM SPSS 27. The results indicate that fashion trends, product quality, and price perception have a positive and significant influence on purchase intention for Modeco Busana products.